Policy Considerations that Could Justify the Enactment of a Crime Victim Compensation Fund in South Africa - Wessels, Bernard (Potchefstroom Electronic Law Journal, 2022)
It may be argued that the current legal position relating to crime victim compensation is unsatisfactory. It should therefore be asked whether there is a potential alternative for crime victim compensation. Many foreign jurisdictions have elected to enact a statutory compensation fund. In its report on the viability of enacting a similar type of fund for crime victims in South Africa, the South African Law Reform Commission stated that a justification for the establishment of a statutory crime victim compensation fund in South Africa remains absent. This article focusses on the justification issue. To determine whether a fund could be established in the South African context the following two-step approach has been outlined. First, a general theoretical framework must be advanced based on which future statutory reform of the law of delict may be justified. Elsewhere I have already done this by identifying policy considerations which the legislature has used to reform specific areas in the law of delict. These considerations include the risk of harm and the concomitant risk of receiving no compensation if the risk of harm materialises; the promotion of the right to social security and the evidentiary difficulties associated with proving fault (in the form of negligence). The second step towards justification is to establish whether these considerations could also justify the proposed development of the law through the enactment of a crime victim compensation scheme in South Africa.